Settling the score the court trials of the Filipino informers and paramilitary collaborators (1945-1952) - Tan, Ma. Felisa S. (Quezon City Departamento ng Kasaysayan, College of Social Sciences and Philosophy, University of the Philippines Diliman, 2009)
During the occupation years, several Filipinos willingly served as informers and paramilitary collaborators of the Japanese. These Filipinos were responsible for the hardships of many guerrilla suspects and other civilians. Some even directly killed these suspects. After the Second World War, it was but natural for the victims to seek retributive justice through the courts for all the crimes that these collaborators committed against them. To settle the score, the Philippine Commonwealth Government established the People's Court and Office of Special Prosecutors to handle and try the cases of all types of Filipino wartime collaborators. Wartime Collaboration was equated with the crime of treason under the Revised Penal Code of the Philippines. The penalty imposed for those who were found guilty of treason ranged from twelve years of reclusion temporal to death. The People's Court was divided into five divisions, with a chairman and one or two Associate Judge/Judges per division. The cases assigned to each division were done by lottery. Most of the Judges appointed to these divisions were either lawyer-politicians and/ or former Court of First Instance judges. Since the cases were assigned by lottery to the People's Court, there were inconsistencies among the five divisions with regard to decisions on cases of a similar nature. The frequent changes in the panel composition of judges in two of the divisions also contributed to these inconsistencies. Moreover, one of the judges openly manifested his bias towards all the wartime collaborators. In the beginning, the newspaper focused on the trials of the prominent political collaborators. In January 1948, however, Pres. Manuel Roxas issued an amnesty for the political, economic and cultural collaborators. The Filipino informers and paramilitary collaborators were not amnestied and their cases continued to be tried by the People's Court until the latter's abolishment in June 1948. The remaining cases were tried by the Courts of First Instance in the different provinces until the next Philippine Pres., Elpidio Quirino issued an amnesty for the Filipino informers and paramilitary collaborators on July 3, 1953.Quite a number of Filipino informers and paramilitary collaborators were sentenced to death by some of the divisions of the People's Court. The Supreme Court, however, only affirmed two death sentences.The High Tribunal usually lacked the number of votes to affirm the death sentences meted out by the lower court to the accused collaborators.
"October 2009."
Thesis (Ph.D. History)--University of the Philippines Diliman.
Keywords: World War, 1939-1945 -- Collaborationists; Philippines -- History -- Japanese occupation, 1910-1945 -- Collaborationists